Analisis Pengaruh Ledakan Populasi Ikan Sapu-Sapu (Pterygoplichthys Spp) Terhadap Pendapatan Nelayan Jaring Insang Di Perairan Danau Sidenreng - Hasrianti Hasrianti; Surianti Surianti; Rini Sahni Puti; Damis Damis; Muhammad Rais Rahmat; St. Hajrah Arif (EnviroScienteae, 2020)
The Sailfin Catfish is one of the invasive fish species. The occurrence of sailfin catfish population explosion in the waters of Lake Sidenreng which disturbs gill net fishermen is one of the main problems that have not been found to solve it. Due to its impact on catch production, catch effectiveness and sustainability of aquatic biodiversity, this research was carried out with the aim of knowing the effect of sailfin catfish population explosion on gill net fishermen's income. This research was conducted for three months, namely from June to August 2020 in Wette'e Village and in the Village of Teteaji Kab. Sidenreng Rappang. The average income of gill-net fishermen before the sailfin catfish population explosion tended to be higher than that of the fishermen after the sailfin catfish population explosion occurred. The highest income of fishermen before the Sailfin catfish population explosion was Rp. 550,000 with the lowest income of Rp. 50,000, while the highest income of fishermen after the sailfin catfish population explosion was Rp. 200,000 with the lowest income of Rp. 15,000. Meanwhile, based on the results of the analysis of the Mann Whitney test, the calculated z value of -1.878 and the Asympe sig (2 tailed) value of 0.060 The significance probability value is lower than ɑ = 0.05. This means that H0 is rejected and H1 is accepted so that it can be concluded that the sailfin catfish population explosion had an effect on fishermen's income before the sailfin catfish population explosion and after the sailfin catfish population explosion occurred.